Commitment Beyond Graduation Through Entrepreneurial Leadership Experience in MBA Program - Nelloh, Liza Agustina Maureen; Hartoyo, Hartoyo; Sumarwan, Ujang; Wirakartakusumah, Aman; Joo, So-Hyun (Aptisi Transactions On Technopreneurship (ATT), 2026)
Alumni commitment acts as a critical component in strengthening the future of higher education, especially within entrepreneurial learning ecosystems. However, limited research has explored alumni commitment through the lens of experience value and alumni satisfaction, particularly in Master of Business Administration (MBA) programs with strong technopreneurship and edupreneurial components. This study investigates how experience value and satisfaction influence MBA alumni commitment at a prominent Indonesian business school. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Importance-Performance Map Analysis (IPMA), the findings reveal that experience value especially utilitarian dimensions embedded in edupreneurial and technopreneurial learning plays a dominant role. Managerially, MBA programs can enhance alumni commitment by integrating executive mentoring, immersive leadership tasks, strategic consulting with real-world firms, and international residencies. These results highlight that entrepreneurial educational experiences, when perceived as valuable and actionable, significantly foster long-term alumni engagement.